Naphthalimide-Buckybowl Tweezer for Selective Recognition of Fullerene C70 - Ghule, Swapnil; Korenkov, Konstantin O.; Sharapa, Dmitry I.; Amsharov, Konstantin Y.; Kataev, Evgeny; Oshchepkov, Alexander S. (Chemistry - A European Journal, 2025)
Supramolecular tweezers-like receptors represent a simple and efficient approach for the molecular recognition of fullerenes. Straightforward synthesis and easy fine-tuning of their geometry are the advantages that allow one to achieve strong binding and specific selectivity. However, the use of buckybowls in constructing tweezers and incorporating fluorescent dyes is still underexplored. To achieve this goal, we have designed mono- and di-substituted receptors by attaching indacenopicene to a naphthalimide dye. The tweezers-like receptor shows the highest selectivity for C70 with an affinity of 2150 M−1, which is about 50-fold stronger than the recognition of C60. DFT and NMR data indicate that the preferred binding mode involves the ellipsoidal C70 molecule coordinating with buckybowls at its poles. In this arrangement, the naphthalimide core establishes two CH–π interactions with the fullerene. The results indicate that conjugating buckybowls with naphthalimides in a suitable design presents a promising method for selective binding and fine-tuning photoinduced electron transfer in the host–guest complex.
CRIS-Team Scopus Importer:2025-04-11
Keywords: buckybowl; dispersion interactions; fullerene; molecular tweezers; naphthalimide